The use of Herbal Body Compress and Warm Belt at the BL 23 meridian point in reducing pain intensity in first-stage labor - Mujahidah, Sa'adah; Astuti, Lestari Puji; Az-zahroh, Khoirin Ni’mah (CV LINK Education Publication, 2024)
Introduction: A preliminary survey at Bhakti Wira Tamtama Hospital Semarang found that the number of deliveries in 2018 was 3,312 deliveries, 2,280 normal deliveries, and 1,032 cesarean section deliveries. The effect of labor pain is prolonged. There were 198 cases of prolonged partus in 2018 (6%). Objective: The purpose of this study was to determine the effectiveness of the use of Herbal Body Compress and Warm Belts in dealing with labor pain in laboring women. Methods: The research design quasi-experiment used pre- and post-tests with the control group. The sampling technique used was accidental sampling with a total sample of 36 respondents divided into 2 intervention groups herbal body compress (n = 18) and warmbelt control group (n = 18). Measurement instrument of labor pain scale using numeric rating scale (NRS). Data analysis using wilcoxon and mann whitney statistical analysis tests with p-<0.05. Result: There is a difference in pain during the first stage in laboring women before and after in the Herbal Body Compress group (P-value = 0.000). There is a difference in labor pain before and after in the Warm Belt group (P-value = 0.001). Conclusion: There are differences before and after treatment, that herbal body compress is more effective in overcoming labor pain than warmbelt (p-value = 0.031) with a mean rank value of herbal body compress 22.19 and warmbelt 14.81. Herbal body compress is effective in reducing labor pain.